R.I.C.E. – An Integrated Model of Welfare Deservingness Perceptions - Knotz, Carlo (My University, 2020)
Research on deservingness perceptions is currently one of the most vibrant areas in the field of welfare state analysis. In this manuscript, we critically assess the state-of-the-art in this field of research and, in particular, the two dominant theoretical approaches, the C.A.R.I.N. framework and the ‘deservingness heuristics’ model. In doing so, we identify some important problems, including conceptual ambiguities and an insufficient explicit integration of the two theoretical models. We suggest a revised and integrated theoretical framework, which we believe provides a way to resolve these issues. Our model suggests four criteria to inform deservingness perceptions: Reciprocity, Identity, Control, and Effort (R.I.C.E.). We provide evidence for our model in the form of vignette experiments administered to online panels in the US and Germany.
Keywords: Welfare state; attitudes; deservingness heuristic; C.A.R.I.N